A simple framework to analyze water constraints on seasonal transpiration in rubber tree (Hevea brasiliensis) plantations - Sopharat, Jessada; Gay, Frederic; Thaler, Philippe; Sdoodee, Sayan; Isarangkool Na Ayutthaya, Supat; Tanavud, Charlchai; Hammecker, Claude; Do, Frederic C. (Frontiers in Plant Science, 2015)
Climate change and fast extension in climatically suboptimal areas threaten the sustainability of rubber tree cultivation. A simple framework based on reduction factors of potential transpiration was tested to evaluate the water constraints on seasonal transpiration in tropical sub-humid climates, according pedoclimatic conditions. We selected a representative, mature stand in a drought-prone area. Tree transpiration, evaporative demand and soil water availability were measured every day over 15 months. The results showed that basic relationships with evaporative demand, leaf area index and soil water availability were globally supported. However the implementation of a regulation of transpiration at high evaporative demand whatever soil water availability was necessary to avoid large overestimates of transpiration. The details of regulation were confirmed by the analysis of canopy conductance response to vapour pressure deficit. The final objective of providing hierarchy between the main regulation factors of seasonal and annual transpiration was achieved. In the tested environmental conditions, the impact of atmospheric drought appeared larger importance than soil drought contrary to expectations. Our results support the interest in simple models to provide a first diagnosis of water constraints on transpiration with limited data, and to help decision making towards more sustainable rubber plantations.